A comparative study between halogen bulb and natural light as light sources during shade selection procedure - Malenab, Emma Marie Antoinette; Piamonte, Karen
This paper aims to find out the effectivity of halogen bulb as a light source during shade selection procedure by comparing it's shade selection score with that of the morning and afternoon light commonly used by UPCD clinicians. The subject for the study were 4th year clinicians. Using the Trubyte Bioform shade guide for plastic denture teeth, they were asked to match three pontics of unknown shades of the same brand under the three light sources. Fifteen subjects were tested for each light source. Statistical analysis revealed that the shade selection score of halogen bulb is not the same as t that of the morning and afternoon light indicating that halogen bulb is not a reliable light source when selecting shades.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Halogen bulb